Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Goat Science 2018
DOI: 10.5772/intechopen.69745
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Passage of Digesta in Ruminants; Are Goats Different?

Abstract: Fluid passage rates through the rumen influence digestion of soluble food nutrients, amount of short-chain fatty acids absorbed in the rumen and that pass out of the rumen, the amount of bypass protein of dietary origin and the amount of microbial protein available to the host as a protein source, making modelling of passage imperative. Current research on passage rate should seek to incorporate various factors that affect rumen fill, and solid and liquid passage rates to develop intake and passage rate predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 119 publications
(229 reference statements)
3
11
0
Order By: Relevance
“…We predicted the without delay liveweight based on herbage availability, season and time off herbage with the supplied data on the levels of accuracy the equations have compared to not using the equation. The current study supports the hypothesis that the quantity of herbage offered [14], physiological state of an ewe [10], as well as environmental factors (such as farm and grazing location) [2,7,8] impact liveweight variation. These factors may interact, which causes the differences between ewes from different farming/grazing locations, physiological state and feeding levels.…”
Section: Validation Stagesupporting
confidence: 86%
See 1 more Smart Citation
“…We predicted the without delay liveweight based on herbage availability, season and time off herbage with the supplied data on the levels of accuracy the equations have compared to not using the equation. The current study supports the hypothesis that the quantity of herbage offered [14], physiological state of an ewe [10], as well as environmental factors (such as farm and grazing location) [2,7,8] impact liveweight variation. These factors may interact, which causes the differences between ewes from different farming/grazing locations, physiological state and feeding levels.…”
Section: Validation Stagesupporting
confidence: 86%
“…Dry matter and fiber increase with herbage density [31]. Higher levels of fiber increase water holding capacity of the gut and thus the rumen clearance [8]. Therefore, it is not surprising that Low herbage had greater DM% and fiber and, thus, the lower rate of ewe liveweight loss.…”
Section: Calibration Stagementioning
confidence: 99%
“…Kennedy et al [ 14 ] reported a decrease in digestibility of organic matter in the rumen (F) with exposure of sheep to AT of −1 to 1 °C and 18 to 21 °C, and was highly correlated to solid digesta passage rate (kp) in the rumen (F = 14.57 kp + 239; R 2 = 0.90, SE = 32.6). Effects of AT on digesta passage rates are equivocal [ 33 ]. Low AT (−1 to 1 °C) caused faster liquid and solid digesta passage rates in sheep compared to high AT (18–21 °C) [ 14 , 15 , 16 ], but did not have an effect on digesta passage rates [ 32 ], while high AT (41 °C) caused faster liquid passage rates compared to low AT (26 °C) in swamp buffalo [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysing the factors that interfere with digestibility, it is observed that, with the use of cactus pear caused a change in the composition of the diet, mainly regarding the proportions of NFC, NDF and CP. The increase in CP content due to the increase of maniçoba in the diets improved the development of ruminal flora and the fermentation process, which can be attributed to the increase in the rate of passage of nitrogenous material to the small intestine (Moyo and Nsahlai, 2017).…”
Section: Discussionmentioning
confidence: 99%